The Effect of Six Weeks of Neuromuscular Training on Joint Position Sense and Lower Extremity Function in Male Athletes with Functional Ankle Instability - Hadi Samadi; Reza Rajabi; Mohammad Karimizadeh Ardakani (Sport Sciences and Health Research)
Lateral ankle sprain is the most common ligament injury in athletes and functional instability is one of the disabling consequences of the ankle sprain. The aim of the current study was to investigate the effect of six weeks of supervised neuromuscular training on joint position sense and lower extremity function in athletes with functional ankle instability. 28 male athletes suffering from functional instability voluntary participated in this study and randomly divided into a training group (n=14) and a control group (n=14). Lower extremity function was measured using Foot and Ankle Ability Measure (FAAM) and FAAM Sport and joint position sense was measured by Ankle Proprioception Goniometer. The data analysis showed had a significant improvement in average absolute error of the reproduction of ankle joint angle in inversion in the experimental group compared with the control group (P<0.05). Also, the training subjects showed a significant improvement in the scores of FAAM and FAAM Sport compared with the control group (P<0.01). Six weeks of progressive supervised neuromuscular training with wobble board and rocker board significantly improved lower extremity function and joint position sense in athletes with functional ankle instability.